Visual Acuity Comparison after Phacoemulsification in Cataract Patients with and without Diabetes Mellitus - Danti Hasanah Fatmawati; Masduki, Imam; Aristiani, Windy (Universitas Ahmad Dahlan, 2024)
Phacoemulsification is a common cataract surgery that improves visual acuity. Postoperative visual outcomes may be influenced by diabetes mellitus (DM). This study aimed to compare visual acuity outcomes after phacoemulsification in cataract patients with and without DM. It used an analytic observational design with a cross-sectional approach, analyzing medical records of 60 cataract patients (30 with DM, 30 without DM). Inclusion criteria were patients with and without DM who underwent phacoemulsification and had visual acuity results 21 days post-surgery. Patients using antidiabetic drugs or insulin were included, while those with incomplete medical records, glaucoma, corneal opacities, cataract complications, diabetic retinopathy, macular degeneration, retinal detachment, hypertensive retinopathy, or chronic kidney disease undergoing hemodialysis were excluded. Data were analyzed using the Mann-Whitney test. Results showed visual acuity in both groups mostly fell within the normal category based on WHO standards (6/6–6/18), with 23 (76.7%) patients in the DM group and 27 (90%) in the non-DM group. Statistical analysis indicated no significant difference in visual acuity between groups (p = 0.150). In conclusion, there is no significant difference in postoperative visual acuity between cataract patients with and without DM undergoing phacoemulsification.